Cross-validation of analytical models for computation of disruption forces in tokamaks. (23rd September 2019) - Isernia, N; Pustovitov, V D; Villone, F; Yanovskiy, V
Abstract: Electromagnetic forces generated during hard-to-predict transient events, represent a serious constraint for the operation and design of tokamaks. A sudden loss of plasma stability, triggering plasma thermal and current quenches, leads to the induction of eddy currents in the conducting structures surrounding the plasma column. Interaction of these currents with the magnetic field is responsible for a j × B local force that might compromise the integrity of the device. Here we evaluate the effect of poloidal currents induced in the wall on the local and global forces. To test the earlier analytical predictions (Pustovitov and Kiramov 2018 Plasma Phys. Controlled Fusion 60, 045011), we consider a circular tokamak by the numerical tool CarMa0NL (Villone et al 2013 Plasma Phys. Controlled Fusion 55, 095008). The results confirm the necessity of incorporating the poloidal currents into the task, as these strongly affect the local stress distribution and the global radial force. The overall agreement between analytical and numerical computation is an additional evidence that CarMa0NL is a sound tool for the prediction of disruption forces in tokamaks. At the same time, the simulation conditions in which the agreement is less satisfactory allow to identify which are the most restrictive assumptions of the analytical model, pointing out the way for future theoretical work.